The Revolutionary Foundations Of The Algerian Educational System And Their Implications (Journal of Namibian Studies : History Politics Culture, 2024)
This article analyzes the content of the revolutionary documents of the Algerian War of Liberation, specifically focusing on the revolutionary foundations of the Algerian national education system derived from this historical period, which spans from 1954 to 1962. These foundational texts are the November 1st, 1954 Declaration, the August 20th, 1956 Soummam Conference, and the Tripoli Charter, issued by the National Council of the Algerian Revolution in June 1962. These documents are seen as future projects and references, expressing the aspirations of the Algerian people for peace, freedom, justice, and progress. The article compares the educational situation at the time these documents were written and then analyzes the extent and nature of their impact on the present and future of the Algerian educational system.The article employs a classical content analysis method, based on verbal analysis as a research unit, to reveal meanings, understand the nature of variables, and define the general goals envisioned by the authors of these documents. As a result, the central issue of this article revolves around showing the strong relationship between the nature of these foundations and the philosophy and strategy of the Algerian educational system, which has undergone various stages of development. The article also explores the impact these foundations had on the present and future of Algeria’s educational system.